Perancangan Sistem Keamanan Ganda Brangkas Berbasis Telegram Menggunakan Mikrokontroler ESP32-CAM - Khozainuz Zuhri; Ahmad Ikhwan (Universitas Mitra Indonesia, 2020)
AbstractThe development of science and technology, especially in the field of Electronics and Information Technology, is expected to improve the technology of room safety systems. Room security system technology usually consists of valuable objects stored in a safe that has a lock system with a number of combination numbers. This safe is placed in a room with many security systems, such as security from security personnel, using laser signal detector technology or with CCTV cameras. However, along with technological developments, this room security system still has weaknesses such as laser light can be seen when it hits particles of dust and cigarette smoke and CCTV cameras are also easily known. Based on this, one of the efforts to secure the safe is to develop technological innovations in the form of remote system notifications and alerts via the telegram application. Based on this, the researcher proposes a safe space security system using a motion detection camera based on esp32-cam with google drive and telegram automatic storage. The result of the research is telegram notification to the user for early warning, which is 5 seconds. In addition, the system is able to receive warning system signals from motion detection results depending on the strength of the internet network..